2010
DOI: 10.1038/ejcn.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

Worsening trend of central obesity despite stable or declining body mass index in Hong Kong Chinese between 1996 and 2005

Abstract: We analyzed the obesity trends in Hong Kong using data from a health assessment program. We recruited 84 357 subjects (27 452 men and 56 905 women; age: mean ± s.d. 49.0 ± 14.7 years, range 20-98 years) in three phases: 5% (25.8, 29.3) and 26.6% (26.0, 27.3), respectively (P: NS). In summary, despite stable or declining BMI, age-standardized central obesity failed to decline in Hong Kong Chinese women and continued to increase in Chinese men over a 10-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 9 publications
3
22
0
Order By: Relevance
“…Our findings are in line with data from Ford et al 24 showing that abdominal obesity continues to rise in the USA despite relative stability in the rate of overall obesity. A study in Hong Kong by Ko et al 25 yielded similar findings. The leveling-off in overall obesity that we found in our study does not imply that the risk of obesity-related diseases will also plateau as abdominal obesity continues to rise.…”
Section: Discussionsupporting
confidence: 73%
“…Our findings are in line with data from Ford et al 24 showing that abdominal obesity continues to rise in the USA despite relative stability in the rate of overall obesity. A study in Hong Kong by Ko et al 25 yielded similar findings. The leveling-off in overall obesity that we found in our study does not imply that the risk of obesity-related diseases will also plateau as abdominal obesity continues to rise.…”
Section: Discussionsupporting
confidence: 73%
“…Data from a study of Hong Kong Chinese found that, between 1996 and 2005, WC had increased despite an apparent plateau in BMI [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In Finnish men and women, mean WC increased by 2.7 cm and 4.3 cm in 15 years while mean BMI did not change much [17]. Lastly, central obesity measured by WC consistently increased in Chinese adult men between 1996 and 2005 while BMI remained unchanged [18]. However, there are few studies examining this in countries early in the nutrition transition.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the age-standardized rate of general obesity (BMI C 25 kg/m 2 ) being 31.0% in men and 18.8% in women in 2005, which are amongst the highest in Chinese communities [10]. In addition, though the rate of general obesity in Hong Kong has stabilized in men and declined in women compared to 10 years ago, the average WC has increased by 1 cm in men and 2 cm in women from 2001 to 2005 with a rate of central obesity of 26.9% in men and 26.6% in women [10]. These high figures herald a looming epidemic of chronic diseases and emphasize the need to monitor the health status of those people with central obesity.…”
Section: Introductionmentioning
confidence: 98%